The structure of apo ArnA features an unexpected central binding pocket and provides an explanation for enzymatic cooperativity. (1st March 2015) - Fischer, Utz; Hertlein, Simon; Grimm, Clemens
<x xml:space="preserve">Abstract</x> The bacterial protein ArnA is an essential enzyme in the pathway leading to the modification of lipid A with the pentose sugar 4‐amino‐4‐deoxy‐L‐arabinose. This modification confers resistance to polymyxins, which are antibiotics that are used as a last resort to treat infections with multiple drug‐resistant Gram‐negative bacteria. ArnA contains two domains with distinct catalytic functions: a dehydrogenase domain and a transformylase domain. The protein forms homohexamers organized as a dimer of trimers. Here, the crystal structure of apo ArnA is presented and compared with its ATP‐ and UDP‐glucuronic acid‐bound counterparts. The comparison reveals major structural rearrangements in the dehydrogenase domain that lead to the formation of a previously unobserved binding pocket at the centre of each ArnA trimer in its apo state. In the crystal structure, this pocket is occupied by a DTT molecule. It is shown that formation of the pocket is linked to a cascade of structural rearrangements that emerge from the NAD+‐binding site. Based on these findings, a small effector molecule is postulated that binds to the central pocket and modulates the catalytic properties of ArnA. Furthermore, the discovered conformational changes provide a mechanistic explanation for the strong cooperative effect recently reported for the ArnA dehydrogenase function.